2010
DOI: 10.5012/bkcs.2010.31.11.3190
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Electrolytes of Organic Solvents and Ionic Liquid for Rechargeable Lithium-Ion Batteries

Abstract: Mixed electrolytes formed by the combination of 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl) imide (BMP-TFSI) ionic liquid and standard liquid electrolyte are prepared and characterized. Linear sweep voltammetry measurements demonstrate that these mixed systems exhibit a wide electrochemical stability window, allowing them to be suitable electrolyte for carbonaceous anode-based lithium-ion batteries. Lithium-ion cells composed of graphite anode and LiCoO2 cathode are assembled using the mixed el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…[30][31][32] To overcome these disadvantages, researchers have introduced the concept of hybrid electrolytes, where an organic solvent is added to the ionic liquid electrolytes so as to increase the room temperature ionic conductivity as well as to get better interfacial behaviour. 15,20,[33][34][35][36] In this work, we have tested hybrid electrolytes composed of 40 wt% ionic liquid in a conventional electrolyte system to understand the role of the ionic liquid in the passivation mechanism of aluminium foil current collector. The proportion of 40 wt% ionic liquid was chosen as a compromise between improved safety and low viscosity for these electrolytes at room temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] To overcome these disadvantages, researchers have introduced the concept of hybrid electrolytes, where an organic solvent is added to the ionic liquid electrolytes so as to increase the room temperature ionic conductivity as well as to get better interfacial behaviour. 15,20,[33][34][35][36] In this work, we have tested hybrid electrolytes composed of 40 wt% ionic liquid in a conventional electrolyte system to understand the role of the ionic liquid in the passivation mechanism of aluminium foil current collector. The proportion of 40 wt% ionic liquid was chosen as a compromise between improved safety and low viscosity for these electrolytes at room temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As can be inferred from the data presented in Table 4, the FILs are unlikely to serve as a single solvent system for the electrolyte application, since their pristine ionic conductivity is already below 274. 34 17.32 3.6 New compound [33] Im 1TFO2 TFSI as mentioned above, the asymmetric structure could increase the lithium ion transport, and hence ionic conductivity. With these attributes of FILs in mind, our research group has synthesized several new FILs [33].…”
Section: Synthesis and Properties Of Specifically Designed Filsmentioning
confidence: 99%
“…We carried out a flammability test called self-extinguishing time (SET) in accordance with a reported study [34]. Each electrolyte was tested three times: The burner was ignited above the sample for 5 s and then switched off.…”
Section: Flammability Testmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Various materials such as lithium metal, carbon, Li 4 Ti 5 O 12 , Si and Sn have been tested as anode materials in ionic liquid-based cells. [4][5][6][7][8][9][10][11][12][13][14][15][16] Among these materials, Li 4 Ti 5 O 12 is considered to be promising, because it exhibits good reversibility with regard to the intercalation/ deintercalation of lithium ions and shows no structural changes during charge-discharge cycling. 13 The ionic liquid electrolytes in the study were found to be irreversibly decomposed on the electrode at a potential that was positive relative to that of the Li/Li + , which resulted in the formation of an unstable solid electrolyte interphase (SEI) on the electrode.…”
Section: Introductionmentioning
confidence: 99%